High quality PVD-MoS2 film on plasma-ALD-SiO2 underlaying material for CFET integration - Matsunaga, Naoki; Imai, Shinya; Shirokura, Takanori; Tsutsui, Kazuo; Kakushima, Kuniyuki; Wakabayashi, Hitoshi (2024 8th IEEE Electron Devices Technology & Manufacturing Conference (EDTM), 2024)
PVD-MoS 2 film on various underlaying materials for a CFET was investigated. It is confirmed that the chemical composition ratio and crystallinity of MoS 2 films are significantly affected by the type of underlying material. A high-quality MoS 2 film was obtained on a plasma-ALD (Atomic-Layer Deposition) SiO 2 film. This result can guide the application of MoS 2 in future electronic systems such as the CFET.